Implementation of Interactive Methods and Creative Media in Enhancing Learning Motivation at PKBM Tahfizh Darussalam - Aulia Syahrani; Risma Ariska Putri; Zahra Nur Adilla; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The background of this research is the importance of increasing student engagement in non-formal education, particularly in Community Learning Centers (PKBM), which often experience problems related to low motivation and participation. The purpose of this study was to analyze non-formal learning methods that can increase engagement by integrating motivation and creativity from tutors. The method used was a descriptive qualitative approach, collecting data through observation, in-depth interviews, and document collection. The study involved five subjects: one PKBM administrator and four tahfidz tutors. The results showed that the use of reinforcement, interactive methods, and creative media can significantly increase student motivation and participation. This improvement is evident in the level of student activity, consistent attendance, and progress in memorization.